HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP HASIL TOLAK PELURU GAYA ORTODOKS SISWA KELAS VIII DI SMP NEGERI 3 BENGKULU TENGAH - Aziz Aziz; Rio andi Saputra Rio andi Saputra; Syisva Nurwita Syisva Nurwita; Supriyanto Supriyanto (Journal of Education and Culture (JEC), 2021)
This study aims to determine the relationship between arm muscle strength and the results of the orthodox bullet repulsion of Grade VIII students at SMP Negeri 3 Bengkulu Tengah. This type of research is descriptive with correlational analysis by looking for relationships between variables and data collection techniques using tests and measurements. The results of this study. Based on data analysis obtained p-value (Sig) = 0.000 <α = 0.05. Based on the above results, it can be concluded that there is a significant (significant) relationship between arm muscle strength and orthodox-style bullet repulsion for grade VIII students at SMP Negeri 3 Bengkulu Tengah.